Hubungan Pengetahuan Dengan Sikap Keluarga dalam Pencegahan Demam Berdarah Dengue (DBD) - Carolina, Putria (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
The incidence of Dengue Hemorrhagic Fever (DHF) has increasedfrom 2021 to 75,538 cases and in 2023 the number of dengue cases increase dagain to 131,265 cases with a deathtoll of 1,135 people. DHF is a disease caused by the Aedes Aegypti mosquito. The family's knowledge of the Mosquito Nest Eradication (PSN) movement greatly influences the family's attitude in preventing dengue fever. Knowledge is the result of knowing and this occurs after people sense an object, the influencing factors are education and age. Attitude is a person's response to a stimulus or stimulation received, the influencing factor is the individual's experience. The higher the family's awareness of preventing dengue fever, the greater the number of cases or incidents of dengue fever in the surrounding environment. This research aims to determine the relationship between knowledge and family attitudes in preventing dengue fever in Menteng District, Palangka Raya City. This research design uses a correlational design with a cross-sectional approach. Accidental sampling technique with a total of 47 respondents. Based on the results of the chi-square test, it was found that p value = 0.021 or a significance level of p < 0.05, then Ha was accepted so that there was a relationship between knowledge and family attitudes in preventing dengue fever in Menteng District, Palangka Raya City.